Bridges between worlds: spirits and spirit work in northern Iceland - Dempsey, Corinne G. ca. 20./21.Jh. (Oxford University Press, 2016)
This work explores the tradition of Icelandic spirit work, known as andleg mal, as practiced in the northern town of Akureyri. Based on firsthand accounts of these spirit encounters, Corinne Dempsey describes how andleg mal's beliefs and practices span not only earth and spirit but Icelandic histories and cross-Atlantic cultures